SWOT analysis for optimizing sustainable agrotourism development in rural hill areas - Eka Rahmatiah Tuwu; Kahirun; La Gandri; La Ode Muhammad Erif; Mustaqiim (Institute of Advance Science, Social, and Sustainable Future, 2025)
Background: Awila Hills Agrotourism is a local agricultural center characterized by diverse horticultural production, including cayenne pepper, curly chili, corn, long beans, pumpkin, mustard greens, and tomatoes. Beyond its role as a tourist attraction, this agrotourism area maintains strong economic linkages with surrounding communities, where local residents regularly purchase fresh agricultural products directly from farmers. This interaction supports a stable local market and strengthens community participation, highlighting the importance of integrated and sustainable agrotourism development. Methods: This study was conducted from April to May 2025 using a mixed-methods approach that combined qualitative and quantitative descriptive analyses. A SWOT analysis framework was applied to identify and evaluate internal and external factors influencing the development potential of Awila Hills Agrotourism, thereby supporting strategic decision-making. Findings: The analysis indicates that the Strength–Opportunity (S–O) strategy achieved the highest priority score of 3.42, making it the most feasible development strategy. This approach emphasizes leveraging internal strengths to capitalize on external opportunities. Key recommended actions include optimizing natural landscapes and visitor comfort through targeted digital media promotion, developing educational tourism packages that integrate agricultural activities with environmental learning, and maintaining cleanliness and comfort to align with government tourism development programs. Conclusion: The prioritization of the S–O strategy underscores the importance of maximizing natural resources and educational potential to increase visitor numbers and enhance local economic benefits. This strategy supports sustainable agrotourism development by balancing tourism growth, community welfare, and environmental conservation. Novelty/Originality of this Article: This study offers a strategic development model for agrotourism by integrating SWOT-based analysis with educational tourism and community economic linkages. The findings provide a practical and replicable framework for sustainable agrotourism development in similar rural and agricultural tourism destinations.